PERENCANAAN PENGEMBANGAN HUTAN MANGROVE DENGAN PENDEKATAN EKOWISATA DI PULAU PENAWAR RINDU KECAMATAN BELAKANG PADANG KOTA BATAM - , MELISA YOHANA SITORUS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Penawar Rindu Island or Belakang Padang is one of the oldest and historic district in Batam Riau Islands province. In terms of natural resources, Belakang Padang island has mangrove ecosystem which has an area of up to 110.5 acres stretching along the sea. In some locations, mangrove condition is still quite good and awake naturalness can be a potential asset for the development of the island territory. The mangrove forest has a forest ecosystem is unique and distinctive, located in tidal areas in the coastal areas, beaches, small islands, and is a potential natural resource potential, if developed as ecotourism. This study aims to analyze and develop the potential of the existing Penawar Rindu island as ecotourism, ecotourism is based on the five principles of conservation, education, economy, tourism, and community participation. The research was conducted by means of observation, interviews, library research, and documentation. Based on this research, it is known that the Penawar Rindu island has species of flora and fauna are diverse, which became one of the attractions that will support tourism, if developed as ecotourism. In addition it has a cultural tourism, religious tourism, marine tourism, shopping tourism, culinary tourism, and special interest tours that attract tourists to visit the Penawar Rindu Island.